Analisis Perbandingan Kinerja Keuangan Perbankan Syariah Yang Melantai di Bursa Efek Indonesia : Studi Kasus Perbandingan Kinerja Keuangan Bank Syariah Indonesia dan Bank BTPN Syariah - taufik, muhammad iman (Jurnal Ilmiah Ekonomi Islam, 2024)
"The Islamic banking industry in Indonesia has experienced rapid growth in recent years. Bank Syariah Indonesia (BSI) and Bank BTPN Syariah are two leading Islamic banks in Indonesia. However, in the post-pandemic era, there has been limited research comparing the financial performance of these two banks. Therefore, this research aims to analyze the financial performance comparison of Islamic banking institutions that have publicly listed their shares on the Indonesia Stock Exchange, namely Bank Syariah Indonesia and Bank BTPN Syariah. The objective of this research is to compare the financial performance between Bank Syariah Indonesia and Bank BTPN Syariah and provide recommendations for investors interested in investing in the Islamic banking sector. This research uses a descriptive-comparative method with a quantitative approach. The data used is secondary data obtained from the financial reports of both banks for the last two years (2021-2022). The measured variables include return on equity (ROE), return on assets (ROA), and price-to-earnings ratio (PER). The data obtained is analyzed using statistical analysis techniques such as t-tests, F-tests, and regression analysis."